BENTUK DAN TIPOLOGI GAMBAR CADAS DI SITUS CERUK LAKANTAGHO I DESA LIANGKOBORI - Mayanti Kasarillah; Abdul Alim; Arie Toursino Hadi (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
The Liangkobori Karst area is known for its many archaeological remains, namely cave sites and niches. The Lakantagho I Niche site is one of several sites in Liangkobori Village that has rock art. This research aims to determine and identify the form and typology of rock art at the Lakantagho I niche Site. The research methods used are primary data collection, secondary data, data recording and data processing. Based on the results of research conducted at the Lakantagho I Niche site,there are 41 panels with a total of 77 images. The images found have different forms of rock art. Among them there are 44 pictures of human forms, 8 pictures of human and fauna forms, 3 pictures of human and boat shapes, 8 pictures of fauna shapes, 1 picture of boat shapes, 7 pictures of geometric shapes and 6 pictures of abstract shapes.Then the results of the type grouping classification carried out were 32 types including MKBMmg2, MKBMtg2, MKMmg2, MKMtg2, MMtg2, MBmg2, MBtg2, MBKtg2, MKBtg1, MKBtg2, MKtg1, MKtg2, MMF1a, MMF1b, MMF2a, MMF3c, MMP 1t12, MMP 1ttl2, MMP2t11, F1, F2, F3, F4, F5, PT2t11,GLC, GCQ, GT, GP, GD, GO and GU, as well as abstract shapes.